Multiple desmoplastic cellular neurothekeomas localized to the face of a 16-year-old boy - García-Gutiérrez, Mónica; Toussaint-Caire, Sonia; Fierro González, Pablo Emilio; Ortíz Hidalgo, Carlos Federico (My University, 2010)
Cellular neurothekeomas are relative uncommon benign dermal tumors of uncertain histogenesis. Most commonly they arise as a solitary papule or nodule on the head and neck or upper trunk of young adults with a slight female predominance. There has been only 1 previous report of multiple neurothekeomas. The patient described herein was a 16-year-old otherwise healthy boy who presented with approximately 30 facial papules that arose over the course of 6 months and progressively enlarged. Histologically, all lesions were composed of spindled to epithelioid cells, but varied in the degree of cellularity and dermal sclerosis. Immunohistochemical staining showed that the cells of interest expressed S100A6, vimentin, CD63 (NKI/C3), PGP 9.5, and factor XIIIa and were negative for CD68, glial fibrillary acid protein (GFAP), S-100, HMB-45, epithelial membrane antigen, actin, and CD57 consistent with a diagnosis of multiple desmoplastic cellular neurothekeomas.© The American Journal of Dermatopathology